Managing pregnancy of unknown location based on initial serum progesterone and serial serum hCG levels: development and validation of a two‐step triage protocol. (9th October 2016) - Van Calster, B.; Bobdiwala, S.; Guha, S.; Van Hoorde, K.; Al‐Memar, M.; Harvey, R.; Farren, J.; Kirk, E.; Condous, G.; Sur, S.; Stalder, C.; Timmerman, D.; et al.
ABSTRACT: Objectives: A uniform rationalized management protocol for pregnancies of unknown location (PUL) is lacking. We developed a two‐step triage protocol to select PUL at high risk of ectopic pregnancy (EP), based on serum progesterone level at presentation (step 1) and the serum human chorionic gonadotropin (hCG) ratio, defined as the ratio of hCG at 48 h to hCG at presentation (step 2). Methods: This was a cohort study of 2753 PUL (301 EP), involving a secondary analysis of prospectively and consecutively collected PUL data from two London‐based university teaching hospitals. Using a chronological split we used 1449 PUL for development and 1304 for validation. We aimed to assign PUL as low risk with high confidence (high negative predictive value (NPV)) while classifying most EP as high risk (high sensitivity). The first triage step assigned PUL as low risk using a threshold of serum progesterone at presentation. The remaining PUL were triaged using a novel logistic regression risk model based on hCG ratio and initial serum progesterone (second step), defining low risk as an estimated EP risk of < 5%. Results: On validation, initial serum progesterone ≤ 2 nmol/L (step 1) classified 16.1% PUL as low risk. Second‐step classification with the risk model selected an additional 46.0% of all PUL as low risk. Overall, the two‐step protocol classified 62.1% of PUL as low risk, with an NPV of 98.6% and a sensitivity of 92.0%. When the risk model was used in isolation (i.e. without the first step), 60.5% of PUL were classified as low risk with 99.1% NPV and 94.9% sensitivity. Conclusion: PUL can be classified efficiently into being either high or low risk for complications using a two‐step protocol involving initial progesterone and hCG levels and the hCG ratio. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.